Outcomes of the CCAFS project Sustainable Intensification of Dairy Production in Indonesia (SIDPI) - Tejaningsih, Safitri (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2021)
Between 2016 and 2020, the project Sustainable Intensification of Dairy Production Indonesia (SIDPI) was carried out in Lembang subdistrict in West Java, Indonesia. The aim of this project was to contribute to increased herd productivity and farmer incomes of Indonesian small-holder dairy farmers, while at the same reducing environmental impacts and improving resource use efficiency. This report describes results of an outcome evaluation of the SIDPI project to identify, describe, verify, and analyze changes brought about by the project, including changes in knowledge, attitude, capacity, policy and practice that occur at different levels. Changes were mainly observed in the primary sector (dairy farmers and dairy cooperative), industry (feed company), an NGO, and the local and international scientific community. Evidence was shown that SIDPI outcomes resulted in reduced environmental pollution and higher resource use efficiency of the dairy sector, and increased milk yields and farmer incomes.